Efektivitas Penyuluhan Terhadap Pengetahuan Ibu Tentang Tersedak Dan Henti Jantung di Ubung Kaja Denpasar Bali - Yustina Ni Putu Yusniawati; Ida Rahmawati; Emanuel Ileatan Lewar (Jurnal Kesehatan Komunitas, 2022)
An emergency condition is a situation that requires quick, precise, and appropriate action to save lives. Delays in providing emergency assistance often occur in children, where the result of this delay is permanent disability and even death. Emergency for children is an important concern because children are not used to expressing uncomfortable conditions in an emergency. Emergency conditions that often occur in children are choking and cardiac arrest. The purpose of this study was to determine the difference in maternal knowledge before and after being given counseling about choking, and cardiopulmonary resuscitation. This study uses a Pre-Experiment with One Group Pre-test Post-test design with a cross-sectional approach. The research was conducted in Ubung Kaja Village. The population in this study were 70 parents who had children aged 0-2 years. Univariate analysis was used to determine the demographic data of the respondents. Bivariate analysis was used to determine differences in maternal knowledge before and after being given counseling about choking and CPR. The results showed that (Choking P 0.000 <a = 0.05), and (Cardiac arrest P 0.000 <a = 0.05). There is an effect of providing counseling on mother's knowledge in emergency handling of fever, choking and cardiac arrest. Further training on emergencies needs to be carried out on an ongoing basis because emergencies can happen anywhere.